Strategic Planning Information System for Improving Quality of Datu Sanggul Hospital in Rantau - Kamarudin Hasan Basri; Erma Suryani (IPTEK Journal of Proceedings Series, 2018)
Datu Sanggul Hospital as one of the institutions engaged in health, has made information technology and information systems as part of business processes that accompany the business trip. Conditions that require unit Management Information System and Medical Record (SIM & RM) to always accompany the institution to be not optimal when the blue print unit SIM & RM service has not been integrated with other units in the planning.This research will make SI / IT strategic plan needed by Datu Sanggul Hospital in Rantau for the current year 2018 to 2022. This research refers to the current condition of SI / TI and analyzed using several approaches to support the process of formulation of strategies that suit the needs.This research was built using Ward & Peppard method. The research step begins by using some analysis such as value chain, five forces, PEST until it can be mapped the position of hospital with SWOT analysis. The Datu Sanggul hospital position was in quadrant IV which applied strength-Threat strategy. Determination of future needs is done by using a balanced scorecard approach to find the appropriate Critical Success Factor needs. Until finally the formulation of the strategy of SI, IT, and IT management to form the portfolio of future applications in the form of 8 new applications, 1 application upgrade and 1 application replace, reliable human resources needed, build cloud computing and standardize governance with Cobit 4.1 and Documentation through ISO 9001: 2008 which is a support for blueprint service for SIM & RM units for 2014 - 2018. The results of this strategic planning will provide direction to management for policy making involving investment, implementation and education required